2009
DOI: 10.1002/adma.200802670
|View full text |Cite
|
Sign up to set email alerts
|

Length‐Dependent Mechanics of Carbon‐Nanotube Networks

Abstract: Fibrous networks comprise a range of materials, from F-actin and tubulin, in eukaryotic cells, [1][2][3] to cellulose, in paper. [4] In the last decade, carbon nanotubes (CNTs) have emerged as a technologically important class of fibers, with nanoscale dimensions of width but micro-to macroscopic dimensions of length. CNT networks enhance the strength, [5,6] conductivity, [7][8][9] and flame resistance [10] of polymer composites, and have a spectacular effect on the rheology of CNT suspensions. [11][12][13][14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 35 publications
(35 reference statements)
5
38
1
Order By: Relevance
“…The statistical length of SWNTs used in our work was in the range of about 5–30 μm; 60% of them were about 15–25 μm, as confirmed by AFM images (Figure S1). Previous reports have concluded that the tensile strength of carbon nanotube network films was influenced by the length of CNTs 33. Films composed of longer CNTs are an order of magnitude stronger than those composed of short CNTs.…”
Section: Resultsmentioning
confidence: 94%
“…The statistical length of SWNTs used in our work was in the range of about 5–30 μm; 60% of them were about 15–25 μm, as confirmed by AFM images (Figure S1). Previous reports have concluded that the tensile strength of carbon nanotube network films was influenced by the length of CNTs 33. Films composed of longer CNTs are an order of magnitude stronger than those composed of short CNTs.…”
Section: Resultsmentioning
confidence: 94%
“…The thermal conductivity of the BN@PE composites has been improved after multistage stretching extrusion process, because the aggregation of BNs were reduced due to the strong shear field [227]. On the contrary, rheological studies showed that the shear could also induce an aggregation of CNTs, and CNTs with a longer aspect ratio possess a larger shear-induced aggregation [228]. The shear-induced distribution of fillers depends on not only the filler but also on the processing details.…”
Section: Improvement Of Filler Distributionmentioning
confidence: 99%
“…The formation of extended networks of particles dispersed in a fluid gives rise to a discontinuous change in the rheological [1][2][3][4][5] and electrical [6][7][8][9] properties of the dispersion at concentrations around the so-called percolation threshold. Historically, percolation theory was first used by Flory [10] to explain the phenomenon of gelation in thermosetting polymers.…”
Section: Introductionmentioning
confidence: 99%